UPAYA PENINGKATAN KINERJA GURU PPPK MELALUI KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, DAN MOTIVASI GURU DI SEKOLAH DASAR NEGERI SE-KECAMATAN SERPONG UTARA - Heru Purwanto; Sri Utaminingsih; Ersam Mahendrawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to analyze the influence of principal transformational leadership, organizational culture, and work motivation, both partially and simultaneously, on the performance of PPPK teachers at elementary schools in North Serpong District. This study employed an associative quantitative research method. The study population consisted of 213 PPPK teachers across 16 schools. The Slovin formula was used as the sampling technique, resulting in a sample size of 139 respondents. The data collection instrument used was a Likert-scale questionnaire that had undergone validity and reliability testing. Data analysis consisted of descriptive analysis and inferential analysis using multiple linear regression. The results showed a positive and significant partial effect between Transformational Leadership on Teacher Performance (t-test 24.442 > t-table 1.977), Organizational Culture on Teacher Performance (t-test 22.238 > t-table 1.977), and Motivation on Teacher Performance (t-test 22.338 > t-table 1.977). Simultaneously, Transformational Leadership, Organizational Culture, and Motivation have a significant effect on Teacher Performance with an Fcount value of 455.219 > Ftable 2.67 and a significance value of <0.001. The Determination Coefficient (R^2) value of 0.910 indicates that the three variables together contribute 91% to the variation in PPPK Teacher Performance, while the remaining 9% is influenced by other factors outside this research model. This indicates that the synergy between inspirational leadership, a healthy school culture, and high work motivation is the main key in optimizing PPPK teacher performance.